Paradoxes of the Inclusion of Afro-descendents and the Multicultural Turn in Latin America - Agudelo, Carlos (2019)
The cultural diversity of human societies and their political management have been the most debated topics by the social sciences in recent times. In Latin America and the Caribbean, we observe the development of mechanisms to recognize different expressions of multiculturality. These forms of inclusion have been accompanied by multiple paradoxes and ambiguities. It is the so-called "multicultural turn" that, although the indigenous peoples have been its most visible protagonist, it has also included the populations of African origin. Based on a synthesis of previous works, the purpose of this text is to present a panoramic view of the presence of people of African descent in Latin America and the Caribbean and the process of gestation and development of multicultural policies applicable to these populations. We will also raise some elements about the limits and obstacles that are observed in the implementation of these policies.